PROFESIONALISME GURU DALAM KURIKULUM BERBASIS ALAM: ANALISIS INTEGRASI PENGALAMAN LUAR RUANGAN TERHADAP CAPAIAN PEMBELAJARAN FORMAL ANAK USIA DINI - Laksmita Wahyu Chandra Utami; Joko Pamungkas (Indonesian Journal of Social Science and Education (IJOSSE), 2026)
Nature based curricula are often perceived as mere aimless play, despite their significant potential to meet formal learning targets. This study aims to analyze the role of teacher professionalism in integrating outdoor experiences (outbound) into formal learning outcomes for early childhood. The research method employed is descriptive qualitative through a literature study of reputable journals. The findings indicate that teacher professionalism, encompassing pedagogical competence and nature-educator identity, is the key to successful integration. Systematically designed outdoor activities are proven to significantly enhance children's executive functions, self-regulation, and literacy-numeracy skills. The discussion emphasizes that direct experience in nature is not a hindrance but a catalyst for formal academic achievements. In conclusion, effective integration requires teachers capable of mapping nature activities into national curriculum indicators. This study recommends specialized training for early childhood teachers to strengthen reflection and curriculum mapping skills in nature-based settings.